2015
DOI: 10.1016/j.oceaneng.2014.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of shock wave focusing in water in a logarithmic spiral duct, Part 1: Weak coupling

Abstract: a b s t r a c tShock focusing in water is a phenomenon that can occur during the impact of a shock wave generated by an underwater explosion onto any type of convergent marine structures. To predict the dynamic material response of the marine structure, it is important to understand the shock wave dynamics during the focusing event. In this paper, both experimental investigations and numerical studies of twodimensional shock focusing in water are presented. Here, a convergent geometry given by a logarithmic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…These comparisons further confirm that the proposed FVS formula and developed program is suitable for the simulation of weakly compressible water flow. We also compared the topological shape of the reflected shock wave with the existing experimental data [27,28], as shown in Figures 6 and 7. We found that the present simulation results based on the FVS-WENO method are consistent with the experimental observations.…”
Section: Validation Of Pulse Hydraulic Fracturingmentioning
confidence: 99%
“…These comparisons further confirm that the proposed FVS formula and developed program is suitable for the simulation of weakly compressible water flow. We also compared the topological shape of the reflected shock wave with the existing experimental data [27,28], as shown in Figures 6 and 7. We found that the present simulation results based on the FVS-WENO method are consistent with the experimental observations.…”
Section: Validation Of Pulse Hydraulic Fracturingmentioning
confidence: 99%
“…#10 The shapes of the various foam geometries include a logarithmic spiral curve; see Figure 6. This particular shape was chosen for its previously shown ability to focus a planar incident shock wave towards its focal point using air, as well as water as the shock propagation medium [34][35][36][37][38]. The logarithmic spiral curve is given by:…”
Section: Time (Ms)mentioning
confidence: 99%
“…Recently, a series of chemical modications have been reported to enhance the performance of soy protein adhesives, such as soy protein structural and crosslinking agent modications. 5 Specically, epoxy and melamine resin, polyisocyanate, polyamidoamine-epichlorohydrin (PAE) resin, phenol formaldehyde resin, trimethylolpropane triglycidyl ether (THPTG), and bisphenol-A waterborne epoxy resin and polyacrylamide (PAM), [6][7][8][9][10][11] were applied to enhance the water resistance of soy protein adhesive due to the crosslinked network structure formed by the reactions with the hydrophilic groups (i.e., -NH 2 , -COOH, and -OH) in soy protein molecules. The resulting adhesives meet the interior use requirements but still rely on unrenewable petroleum-based resources.…”
Section: Introductionmentioning
confidence: 99%